On a strategy of economic security - S. V. Kazantsev (Мир новой экономики)
On April 29, 2016 marks the 20th anniversary of the adoption of the State Strategy of Economic Security of the Russian Federation. It began to work in a difficult period of formation in Russia of new socio-economic relations. A number of industrialized countries and major international corporations tried to use the difficulties of development of the Russian Federation and, the weakening of its position in the world economic space in their economic and political interests, which conflict with the interests of Russia and its economic entities. The aim of the Strategy was to protect the development of the Russian economy and welfare of the citizens from internal and external threats. It was assumed that the Strategy will work during the period of economic transformation, which will last from three to five years. It’s time to elaborate and adopt a new State strategy of economic security of the Russian Federation. The article contains results of the author’s analysis of the National Security Strategy, the State Strategy of Economic Security of the Russian Federation and of the Russian Federation law «On security». Rely on these documents and based on the study of contemporary threats to security of Russia, the author offers to include in the text of the State Strategy of Economic Security of the RF the following sections: 1) general statements, 2) securable objects, 3) threats to economic security of the Russian Federation and, 4) the sources of threats and threatening actors, 5) responsible for the protection (guardians) and their responsibility, 6) means, tools and methods of protection, 7) conditions and time of their application, 8) indicators of threats and of a level of security, 9) monitoring threats and security.